“Kama muta” or ‘being moved by love’: a bootstrapping approach to the ontology and epistemology of an emotion - Fiske, A. P. (2018)
The emotion that people may label being moved, touched, having a heart-warming experience, rapture, or tender feelings evoked by cuteness has rarely been studied and is incompletely conceptualized. Yet it is pervasive across history, cultures, and contexts, shaping the most fundamental relationships that make up society. It is positive and can be a peak or ecstatic experience. Because no vernacular words consistently or accurately delineate this emotion, we call it kama muta. We posit that it is evoked when communal sharing relationships suddenly intensify. Using ethnological, historical, linguistic, interview, participant observation, survey, diary, and experimental methods, we have confirmed that when people report feeling this emotion they perceive that a relationship has become closer, and they tend to have a warm feeling in the chest, shed tears, and/or get goosebumps. We posit that the disposition to kama muta is an evolved universal, but that it is always culturally shaped and oriented; it must be culturally informed in order to adaptively motivate people to devote and commit themselves to new opportunities for locally propitious communal sharing relationships. Moreover, a great many cultural practices, institutions, roles, narratives, arts and artifacts are specifically adapted to evoke kama muta: that is their function.